Viral Outbreaks Global Impact and Newer Horizons - Saxena, Shailendra K. (IntechOpen, 2023)
This book offers a comprehensive overview of recent trends in viral outbreaks, covering general concepts of immunobiology of infections, viral outbreaks, pathology, virology, viral genomics, viromes, and antiviral pharmacology. It also discusses current clinical recommendations for managing various viral diseases, highlighting ongoing issues, recent advances, and future directions in diagnostic approaches and therapeutic strategies. The book focuses on various aspects and properties of viral outbreaks, whose in-depth understanding is crucial to protect humanity from further losses of resources and economies due to viral diseases. It provides an overview of recent developments in the detection, monitoring, treatment, and control of several viral diseases that have caused recent epidemics or pandemics.